INTERPRETASI SISTEM PANAS BUMI GUNUNG TELOMOYO BAGIAN UTARA KABUPATEN SEMARANG BERDASARKAN DATA GEOMAGNET - Hiskia Anggit Maulana; Tony Yulianto; Udi Harmoko (Youngster Physics Journal, 2014)
Research has been carried out using the magnetic methods that have aim for interpret the subsurface structure of Telomoyo Mount geothermal field. The second aim is for analysis the model of Telomoyo Mount geothermal field previous.Magnetic data acquisition has been carried out in 83 points by using a couple of PPM (Proton Precession Magnetometer). Those are a PPM GSM19T model geometric is used looking for total magnetic anomaly and the second one is PPM G856X model that used as a base station. Then the result of acquisition data is processed by the daily correction and IGRF (International Geomagnetic Reference Field) correction. The corrected data is used to create total magnetic anomaly contour. Magnetic field that negative values is the research target and then do subsurface cross section that looking for visualization of conceptual geothermal model of Telomoyo Mount by processing of upward continuation and reduction to pole.The result of study showed a pair of positive and negative closure that indicating a fault under surface zone. In 2D modeling result is about 1400 meters depth. In 800 to 1400 meters depth can be interpret as a clay cap with a low susceptibility parameter that valued  -0.313 x 10-3 (SI-unit).Keywords: Geothermal, Telomoyo Mount, total magnetic field